2018
DOI: 10.1158/2159-8290.cd-17-1263
|View full text |Cite
|
Sign up to set email alerts
|

A Secondary Mutation inBRAFConfers Resistance to RAF Inhibition in aBRAFV600E-Mutant Brain Tumor

Abstract: BRAF hyperactivates ERK and signals as a RAF inhibitor-sensitive monomer. Although RAF inhibitors can produce impressive clinical responses in patients with mutant tumors, the mechanisms of resistance to these drugs are incompletely characterized. Here, we report a complete response followed by clinical progression in a patient with a-mutant brain tumor treated with dabrafenib. Whole-exome sequencing revealed a secondary mutation at progression that was not present in the pretreatment tumor. Expressing BRAF in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 54 publications
1
44
0
Order By: Relevance
“…Until recently, secondary BRAF mutations such as to cause BRAF and MEK inhibitor resistance could not be detected, whereas the selective amplification of mutant BRAF was detected in colorectal cancer cell lines that are resistant to the MEK inhibitor [77] as a result of an underlying mechanism of MEK1 hyperactivation. However, whole exome sequencing recently led to the detection of a secondary mutation in mutant BRAF, which confers resistance to RAF inhibitor [78], in a brain tumour that was progressing though not before the tumour was treated. A secondary BRAF resistant mutation was also detected in metastatic BRAF mutant melanoma [79] using detailed imaging studies and genetic analyses.…”
Section: Mek/erk Inhibition and Erk Reactivationmentioning
confidence: 99%
“…Until recently, secondary BRAF mutations such as to cause BRAF and MEK inhibitor resistance could not be detected, whereas the selective amplification of mutant BRAF was detected in colorectal cancer cell lines that are resistant to the MEK inhibitor [77] as a result of an underlying mechanism of MEK1 hyperactivation. However, whole exome sequencing recently led to the detection of a secondary mutation in mutant BRAF, which confers resistance to RAF inhibitor [78], in a brain tumour that was progressing though not before the tumour was treated. A secondary BRAF resistant mutation was also detected in metastatic BRAF mutant melanoma [79] using detailed imaging studies and genetic analyses.…”
Section: Mek/erk Inhibition and Erk Reactivationmentioning
confidence: 99%
“…The IC 50 value of the resistant line M238R1 was significantly higher than that of the parental line M238. Previous studies indicated that secondary mutations in BRAF could lead to BRAFi resistance [10] . To rule out the possibility that secondary mutations in BRAF lead to BRAFi resistance in M238R1, we sequenced the BRAF coding region in M238R1.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, it is critical to investigate the mechanisms underlying drug resistance and design alternative therapeutic strategies to overcome drug resistance. Resistance to kinase inhibitors is often associated with secondary mutations in the target genes, which render the kinase insensitive to the inhibitor [10] . However, we did not find secondary mutations in BRAF coding regions in the M238R1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of the BRAF gene leads to the formation of large amounts of the BRAF protein, and this may result in dimerization. Surprisingly, to the best of our knowledge, no secondary mutations in BRAF have been found in melanomas, though there is an example of a BRAF secondary mutation in a V600E brain tumor [ 118 ], namely L514V, and in this case it conferred resistance to dabrafenib. Moreover, BRAF inhibitors bind one BRAF and transactivate the other one, decreasing the effectiveness of treatment with BRAF inhibitors.…”
Section: Discussionmentioning
confidence: 99%